Winning the Third World : Sino-American Rivalry during the Cold War - Brazinsky, Gregg (Book collections on Project MUSE., 2017)
'Winning the Third World' examines afresh the intense and enduring rivalry between the United States and China during the Cold War. Gregg A. Brazinsky shows how both nations fought vigorously to establish their influence in newly independent African and Asian countries.